1992
DOI: 10.1007/bf02537058
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide, an inhibitor of lipid oxidation by lipoxygenase, cyclooxygenase and hemoglobin

Abstract: The present study demonstrated that nitric oxide, which is an important mammalian metabolite, can inhibit oxidation by lipoxygenase, cyclooxygenase and hemoglobin. The inhibition is manifested as a lag-phase that is reversible. The inhibitory effect of nitric oxide on lipoxygenase and cyclooxygenase seems to derive from i) the capability of .NO to reduce the ferric enzyme to the ferrous form, which is inactive; ii) competition for the iron site available for exogenous ligands; and iii) the radical scavenging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(123 citation statements)
references
References 43 publications
6
117
0
Order By: Relevance
“…Prolongation of the lag phase with a longer presence of NO in the reaction mixture suggests that NO interacts with the rabbit 15-lipoxygenases and converts it to an enzyme species which is less susceptible to product activation. A similar kinetic behaviour has been reported for the soybean lipoxygenase during its interaction with NO [7,201. A possible mechanistic reason for this lower susceptibility towards peroxide activation is the formation of a ferrous lipoxygenase-NO complex.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Prolongation of the lag phase with a longer presence of NO in the reaction mixture suggests that NO interacts with the rabbit 15-lipoxygenases and converts it to an enzyme species which is less susceptible to product activation. A similar kinetic behaviour has been reported for the soybean lipoxygenase during its interaction with NO [7,201. A possible mechanistic reason for this lower susceptibility towards peroxide activation is the formation of a ferrous lipoxygenase-NO complex.…”
Section: Resultssupporting
confidence: 82%
“…It has been reported before that the soybean lipoxygenase is inhibited reversibly by NO [7], but no detailed kinetic analysis of this effect has been performed. Because of the structural and kinetic similarities of plant and animal 15-lipoxygenases it was straightforward to assume that mammalian 15-lipoxygenases are also inhibited by NO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that nitric oxide may reversibly interact with the rabbit 15-1ipoxygenases and convert it to an enzyme species which is less susceptible to peroxide activation. A similar kinetic behaviour has been reported before for the soybean lipoxygenase-1 [6,8]. Furthermore, we found that the length of the lag period did depend on the NO concentration (not shown).…”
Section: Kinetic Studiessupporting
confidence: 90%
“…28 Additionally, methemoglobin binds ⅐ NO to form a nitrosyl-hemoglobin ( ⅐ NO-Hb) intermediate that loses its ability to oxidize linoleic acid and produce conjugated dienes as well as the ability to co-oxidize substrates such as ␤-carotene. 29 In general, when ⅐ NO complexes with metalloproteins, lipids are protected from further oxidation by metals and oxidant metabolites of ⅐ NO. However, the relative extent of this reaction in oxidizing membranes and lipoproteins is unclear, because the rate of ⅐ NO reaction with oxidationpropagating species such as LOO ⅐ is 10…”
Section: No Can Modulate Lipid Oxidation By Reacting With Cellular Prmentioning
confidence: 99%